Mitogenome of Anterastes babadaghi (Orthoptera: Tettigoniinae; Platycleidini): Frequent conserved overlapping regions within Tettigoniinae - Karşi, Uğur; Çiplak, Battal (Zootaxa, 2019)
Development of next generation sequencing rapidly increased the number of total mitogenome in data bases. However, the documented number of total mitogenome from species of Tettigoniinae is still limited and a comparison at subfamily level has not been made sufficiently. This paper aims to describe total mitogenome of A. babadaghi (Orthoptera, Tettigoniidae) by comparing to the known mitogenomes of other Tettigoniinae. The total mitogenome of A. babadaghi is 15882–15883 bp, AT skewed with 70.2% AT percentage, and consists of 13 protein coding genes (PCG), 22 tRNA genes, two rRNA genes and an AT rich control region. The genes are ordered as in pancrustacean. The comparative description of mitogenomes in Tettigoniinae showed that total length varies between 15766-16788 bp, the start codon for protein coding genes almost always fits to the ATN pattern, the stop codons are incomplete T-- / TA- and rarely complete TAA, intergenic spacers (IGS) and overlapping regions (OR) in species of the subfamily are similar in number, location, length and nucleotide sequence. We arrived to following conclusion from comparative data: (i) A. babadaghi has a typical orthopteran mitogenome by general features; (ii) this generalisation seems valid for Tettigoniinae as gene content, gene location, gene order, average AT content, anticodons and secondary structure of the tRNA genes, the start and stop codons of the protein coding genes, and several IGSs/ORs are similar to other orthopteran and hexapopods, (iii) variation range in total mitogenome length is narrow in Tettigoniinae and mainly determined by the lengths of control region and total IGSs, (iv) mitogenome of the subfamily exhibits conserved patterns especially in overlapping regions, but conserved features are mostly plesiomorphic.